Stevens' Poetry of Existence and Being: The Existential Poetry and Philosophical Influence of Wallace Stevens (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Wallace Stevens (1879-1935) by the current criticalreckoning is an outstanding poets' poet and his influence is unmistakable inthe world of international English poetry both as a thinker and as aninnovator. He has demonstrated in his work how a philosophical idea becomestransmuted into poetry. As Nabokov said, Wallace Stevens shows how poetry byitself becomes the highest form of truth. Wallace Stevens maintained a uniquepersonal temper which can be compared to that of existential thinkers. In thepoetry of Wallace Stevens the subject as a relation is stressed and the world'sobjectivity is left to itself intact almost in an existential context.